Pitfalls in vertical arrangements - Gianpaolo Rossini; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
A popular way of obtaining essential inputs requires the establishment of an input production joint venture (IPJV) in the upstream (U) section of the vertical chain of production by firms competing and selling final goods in the downstream (D) section of the vertical chain. In spite of the apparently simple arrangement there are many possible governances for the management of the IPJV according to the ownership structure and to the degree of delegation granted to the IPJV by parent firms. We explore the best sustainable governance arrangement for the IPJV. We address this question in a duopoly framwork and we find a large area of impossible vertical arrangements associated with technological asymmtery. The most likely governance of the vertical arrangment associated to the IPJV is total independence.
Keywords: L24; L42; 330